Social Networks in Late Hellenistic Northern Etruria: From a multicultural society to a society of partial identities - Raffaella Da Vela (Digital Classics Online)
This contribution concerns the perception of local cultural identities in Hellenistic Northern Etruria. I aim to answer the following question: how did the evolution of the economic and politic relationships between settlements condition the perception and the expression of the local identities? During the Romanization, the Region of my case study presents a complexity of patterns, as result of the interaction of local needs and backgrounds with the global process of institutional and economic unification of the Mediterranean following. The Social Network Analysis (SNA) has been chosen as methodology to approach this complexity. I propose some parameters to detect local identity markers, then I present an integrated method to relate their development to the evolution of the relational networks between the communities.